Analysis of the Use of Digital Marketing as a Media for Marketing Business Results in Border Areas Between Countries (Study of Banana Business Actors in Malacca Regency) - GIE, Emilia; SARONG, Yohanis S.; GIRI, Erna; FOEH, Ricky Ekaputra; NATONIS, Sari A. (PT Keberlanjutan Strategis Indonesia, 2024)
The digital era and the Industrial Revolution 4.0 have had an impact on people's lives, especially in the marketing of banana commodities in Malaka Regency, one of the districts that shares a land border with the State of Timor Leste. The method used in this research is a descriptive method with a qualitative approach with a total of 60 informants who were determined purposively then the collected primary and secondary data were analyzed using data analysis techniques from Creswell (2016). The research results found the use of digital marketing as a media for marketing business results in border areas between countries by banana business actors in Malacca Regency, so the author uses digital marketing indicators by Nasdini (2012:32) which are constrained by aspects (a) internet network accessibility, (b) interactivity with the absence of two-way communication between producers and consumers and (c) entertainment which is still minimal, while the inhibiting factors for the use of digital marketing as a media for marketing business results in border areas between countries by banana business actors in Malacca Regency are; (a) internet infrastructure, (b) don't have a smartphone, (c) no workforce to deliver products to consumers outside the village, (d) don't know the market place.